RANCANG BANGUN SISTEM KENDALI TINGGI MUKA AIR PADA TANDON DENGAN WATER LEVEL CONTROL OMRON 61F-G-AP BERBASIS INTERNET OF THINGS (IOT) - Ma’aliyal Ulya, Ahmad; Duta Nugraha, I Putu Elba; Raka Agung, IGAP. (Jurnal SPEKTRUM, 2024)
The importance of maintaining the expansion of the water supply system needs to be increased to provide each individual's daily clean water needs. The Agroindustry was reliable in providing clean water itself. Sekar Anugrah Penglipuran was one of the Agroindustry in Penglipuran, Bangli that required a huge water supply. This issue could be supported by applying water level control technology to prevent wasting water. Water level control (WLC) is a modern technology system that is able to control and maintain the water capacity level as required automatically. This research aims to analyze the working and wiring of the IoT-based WLC Omron 61F-G-AP and its application in the agro-industrial sector of Sekar Anugrah Penglipuran. This research includes the design and construction of a control system with planning, design, and testing stages for 7 days with technical analysis. Based on the test, there is a difference in the results of the volume calculation with data obtained from the Thingspeak website. The value of volume differences between manual calculation and IoT system calculation because there is a decimal scale in the manual calculation and IoT system calculations are integer so it produces differences in calculation.